Pengembangan kreativitas melalui permainan menyusun balok pada anak kelompok b tk islam terpadu sabilillah dompilan sukoharjo tahun ajaran 2014/2015 - Trisnawati, Emy (2016)
ABSTRACT A CREATIVITY DEVELOPMENT THROUGH THE GAME OF ARRANGING BARS IN CHILDREN OF GROUP B OF TK ISLAM TERPADUSABILILLAH DOMPILAN SUKOHARJO IN THE ACADEMIC YEAR OF 2014/2015 Emy Trisnawati. A. 520100122. Department of Early Age Children Education. Teacher Training and Education Faculty. Muhammadiyah University of Surakarta. 2015. xiv + 87 pages + attachments. The objective of this research was to develop creativity through the game of arranging bars in the children of Group B of TK Islam Terpadu (the Islamic Integrated Kindergarten) Sabilillah Dompilan Sukoharjo in the Academic Year of 2014/2015. Kind of this research was a kind of Class Action Research. Subjects of this research were the children of Group B of TK Islam Terpadu Sabilillah Dompilan Sukoharjo with the amount of 20 children.The data collected were data on the children's creativity and the data on the learning implementation through the method of game of arranging bars. The technique of data collection used observation. The technique of data analysis used the technique of comparative analysis and the technique of interactive analysis. Based on the results of the research, it could be concluded that the learning using the game of arranging bars could increase the creativity of the children in TK Islam Terpadu Sabilillah Dompilan Sukoharjo in the Academic Year of 2014/2015. It was showed by the existence of an increase in the average percentage of the development of the children's creativity before the action that was 35.00% that meant that the children were not creative, the cicle I reached 62.19% that meant that the children were creative, and in the cicle II reached 89.38% that meant that the children were very creative. Keywords:Creativity, Game of Arranging Bars